The new trends in SPD processing to fabricate bulk nanostructured materials - Valiev, R.Z. (Физика и техника высоких давлений, 2006)
During the last decade severe plastic deformation (SPD) has become a widely known method of materials processing used for fabrication of ultrafine-grained materials with attractive properties. Nowadays SPD processing is rapidly developing and is on the verge of a transition from lab-scale research to commercial production. This paper focuses on several new trends in the development of SPD techniques for effective grain refinement, including those for commercial alloys, and presents new SPD processing routes to produce bulk nanocrystalline materials.